Improvement of Phosphorus Removal from Wastewater Through Fermentation of Low-Concentrated Wastewater Sludge and Increased Production of Volatile Fatty Acids - Elena Gogina; Nikolay Makisha; Igor Gulshin; Anna Reshetova (Limnological Review)
This article presents the results of a two-stage study: the first stage involved assessing the dependence of the increase or decrease in the concentration of volatile fatty acids (VFAs) on external factors and then assessing the relationship between the VFA concentration in the supernatant after fermentation and the processing characteristics (temperature, mixing mode, alkalinity, pH, nitrogen and phosphorus content). The greatest increase in VFAs (content up to 285 mg/L in the supernatant) was achieved at a temperature in the range of 28 to 38 °C with constant mixing of the sludge. Based on the results of the second stage, a conclusion was made on the efficiency of using a particular substrate depending on the concentration of phosphorus phosphates in the incoming wastewater. The study results showed that 7.54 mg/L of phosphorus can be removed with a given probability (for activated sludge, raw sludge and wastewater). It is recommended to compensate for the excess of this concentration by dosing the acetic acid solution at a rate of 3800 meq/L of VFA per 1 mg/L of phosphorus phosphates. The literature does not contain any results of parallel studies of the operation of a controlled bioreactor with artificial external feeding and acidified VFA. The results of the study can be applied in planning sludge acidification systems in the technological scheme of wastewater treatment and sludge processing.